The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/cod.13042
|View full text |Cite
|
Sign up to set email alerts
|

Hand eczema and occupational contact allergies in healthcare workers with a focus on rubber additives

Abstract: Contact allergy to rubber additives in medical gloves is the most common cause of occupational allergic contact dermatitis in HCWs. Aimed patch testing with relevant rubber additives is mandatory when HE in HCWs is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 52 publications
2
37
3
2
Order By: Relevance
“…The authors concluded that DPG was a relevant contact allergen in sterile polyisoprene gloves, contrasting with an older study suggesting that most positive reactions to DPG were probably attributable to irritation, and were therefore false positives . A recent study by Hamnerius et al reported a large number of positive reactions to DPG, which were slightly more numerous than positive reactions to thiuram mix. Consequently, only DPG‐free medical gloves are now used in the respective hospital.…”
Section: Discussionmentioning
confidence: 89%
“…The authors concluded that DPG was a relevant contact allergen in sterile polyisoprene gloves, contrasting with an older study suggesting that most positive reactions to DPG were probably attributable to irritation, and were therefore false positives . A recent study by Hamnerius et al reported a large number of positive reactions to DPG, which were slightly more numerous than positive reactions to thiuram mix. Consequently, only DPG‐free medical gloves are now used in the respective hospital.…”
Section: Discussionmentioning
confidence: 89%
“…Considerable sex differences were observed in most of the industrial activities. In particular, cleaners, hairdressers, barbers and beauticians, and healthcare workers were confirmed as occupational categories with a highly female dominance, whereas construction workers were a strictly male category 9,51,57,64,65 …”
Section: Discussionmentioning
confidence: 97%
“…Accelerators are the most common cause of contact dermatitis due to rubber gloves. Hamnerius et al have reported that the allergens responsible for allergic contact dermatitis is as common for diphenylguanidine as it is for thiurams. However, it is also true that chemicals that are not accelerators have been reported to also cause contact dermatitis .…”
Section: Discussionmentioning
confidence: 99%